HUBUNGAN POLA ASUH ORANG TUA TERHADAP KEPERCAYAAN DIRI PADA ANAK TUNA RUNGU DI SLB KOTA JAMBI - Elisa Murti Puspitaningrum (JURNAL KEBIDANAN, 2018)
Deaf is a condition in which can’t hear a sound. A deaf child is always suspicious to his environment, which often resulted in a lack of self-confidence so that proper parenting is required to enhance self-confidence of the children. With patience and personal understanding of the child, parents can help children have confidence in the environment. The purpose of this study was to determine the correlation between parenting pattern and self-confidence on deaf children at SLB Jambi City. This reseach used descriptive correlation study with cross sectional design. Population was used 34 students at SLB Jambi City and the sampling technique used was total sampling. Data obtained by using a questionnaire on January 2018 This study used primary data in data collection and Chi Square Test in data analysis with the result α = 0.05 Results of study indicated that parents who implements democratic parenting for their children as many as 19 children (55,9%), and who having good self-confidence was equal to sufficient one with total of 12 children (35,3%). Based on Chi Square test there was a correlation between parenting pattern and self-confidence on deaf children at SLB Jambi City (p-value : 0,023) It rrecommended for the school and cparents to improve guidance and education for their deaf children to establish better self-confidence